Review on key technologies for coordinated operation of microgrid cluster - LOU Guannan; WANG Lei; LIN Da; DU Yuhua (Zhejiang dianli, 2025)
Multi-microgrid systems （MMSs）， as a crucial approach to address the challenges of large-scale distributed renewable energy （DRT） accommodation and enhance the efficient interaction between generation， grid， load， and storage， can alleviate the adverse impacts of renewable energy’s intermittency and randomness on users and power grids. They are an essential component of the future energy internet. With the large-scale integration of distributed renewable energy （DRE）， the operational complexity and control difficulty of microgrid cluster significantly increase. A reasonable multi-source coordinated control strategy is critical to ensuring the stable， reliable， and efficient operation of the system and is also the foundation for achieving optimal configuration and intelligent scheduling. Based on existing research findings， this paper elaborates on the classification and interconnection methods of microgrid cluster， summarizes the development status of key technologies such as coordinated control strategies under different scenarios and their stability analysis， and provides an outlook on the development trends of MMSs.